Applying the jigsaw learning method to structural kinesiology - Early, Kate S.; Williams, Josie; Saltarelli, William A. (Advances in physiology education, 2025)
The jigsaw learning approach divides complex anatomical concepts into manageable subtopics for students to learn in small groups. This method then fosters collaborative learning and peer teaching to communicate subtopics to others, putting together the whole puzzle of a concept. By assuming dual roles as learners and teachers, students develop critical thinking, communication, and teamwork skills. We provide a detailed framework for implementing jigsaw learning in undergraduate structural kinesiology courses. The jigsaw method is a cooperative learning strategy that allows students to assume dual roles as both learners and teachers. Jigsaw encourages individual accountability and engagement with peers to drive learning, leading to a collaborative environment that emphasizes communication and teamworking skills. Anatomy is often a difficult subject for students, considering the detail and volume of information covered. We outline the jigsaw method for an undergraduate structural kinesiology course, where students first formed learning groups to master specific anatomical topics before regrouping into teaching groups to share their knowledge. To enhance the impact of the jigsaw method, we discuss common challenges to the technique and how to overcome these barriers. Thus, we aim to display the potential of the jigsaw method to foster a supportive learning environment in structural kinesiology, despite limitations, to enhance student engagement and learning. NEW & NOTEWORTHY The jigsaw learning approach divides complex anatomical concepts into manageable subtopics for students to learn in small groups. This method then fosters collaborative learning and peer teaching to communicate subtopics to others, putting together the whole puzzle of a concept. By assuming dual roles as learners and teachers, students develop critical thinking, communication, and teamwork skills. We provide a detailed framework for implementing jigsaw learning in undergraduate structural kinesiology courses.